2011
DOI: 10.1007/s00231-011-0938-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of turbulence intensity on film cooling of gas turbine blade from trenched shaped holes

Abstract: This paper reports a computational investigation on the effects of mainstream turbulence intensity on film cooling effectiveness from trenched holes over a symmetrical blade. Computational solutions of the steady, ReynoldsAveraged Navier-Stokes equations are obtained using a finite volume method with k -e Turbulence model. Whenever possible, computational results are compared with experimental ones from data found in the open literature. Computational results are presented for a row of 25°forward-diffused film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 18 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…They also concluded that the adiabatic effectiveness with the narrow trench was relatively constant across this range of blowing ratios. However, these results were inconsistent with Harrison et al [15], Shuping [16], Baheri Islami and Jurban [17], and Lu and Ekkad [18], which stated that when the blowing ratio increased from 0.6 to 1.4, the performance of the trench was three times greater than that for baseline cylindrical holes. Recently, Ai et al [19] proved that trenching reduced the coolant momentum ratio and impaired the effectiveness while traditional cooling holes performance was better at low blowing ratios.…”
Section: Introductionmentioning
confidence: 75%
“…They also concluded that the adiabatic effectiveness with the narrow trench was relatively constant across this range of blowing ratios. However, these results were inconsistent with Harrison et al [15], Shuping [16], Baheri Islami and Jurban [17], and Lu and Ekkad [18], which stated that when the blowing ratio increased from 0.6 to 1.4, the performance of the trench was three times greater than that for baseline cylindrical holes. Recently, Ai et al [19] proved that trenching reduced the coolant momentum ratio and impaired the effectiveness while traditional cooling holes performance was better at low blowing ratios.…”
Section: Introductionmentioning
confidence: 75%
“…Most research has been done by the RANS approach with the k –ε $\varepsilon $ turbulence method to simulate the film cooling of the typical blades 12 . The main parameters involved in the film cooling phenomena (blowing ratio, turbulence intensity, hole angle, hole geometry, in stagger and in‐line hole arrangement, hole to hole distance, coolant velocity, and temperature) are examined in various studies 13–25 …”
Section: Introductionmentioning
confidence: 99%
“…Saumweber et al 23 experimentally studied the film cooling effectiveness by applying two different turbulence intensities on shaped holes. Baheri Islami et al 24 conducted the influence of four different turbulence intensities (0.5%, 2%, 4%, 10%) and blowing ratios ( M = 0.3, 0.5, 0.9, 1.3) on film cooling performance of trenched holes' shape on AGTB blade. Their results showed that trenched‐shaped holes for all ranges of blowing ratios have better film cooling performance.…”
Section: Introductionmentioning
confidence: 99%
“…In the downstream of a single row of film cooling holes, the cooling effectiveness drops due to the mixing of mainstream and coolant flow. Meanwhile, most of the film cooling correlations in published literatures were mostly focus on the blowing ratio (BR), inclined angel, the shape of the hole and so on (Goldstein et al, 1974;Gritsch et al, 1998;Hasan et al, 2003;Heidmann & Ekkad, 2008;Islami & Jubran, 2012;Islami et al, 2010;Khajehhasani & Jubran, 2016;Ming Li & Hassan, 2015;Yuen & Martinez-Botas, 2003). In the film cooling process, abundant vortex structures are generated and transported owing to the interaction between the jet flow and the cross flow (Kelso et al, 1996).…”
Section: Introductionmentioning
confidence: 99%